2010
DOI: 10.1001/archpediatrics.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Wheezing in the Third Year of Life Among Children Born at 32 Weeks' Gestation or Later

Abstract: To quantify the relationship between recurrent wheezing (RW) in the third year of life and respiratory syncytial virus (RSV) infection, prematurity, and neonatal oxygen exposure. Design: Retrospective cohort study linking inpatient, outpatient, and laboratory databases for cohort assembly and logistic regression analysis. Setting: Integrated health care delivery system in Northern California. Participants: A total of 71 102 children born from 1996 to 2002 at 32 weeks' gestational age or later who were health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…Recurrent wheezing: ≥3 episodes of bronchial obstruction not verified by a physician1 and 3At 1 year:Asthma (mean: 11% vs. 0% ( P = 0.004)Recurrent wheezing (mean: 4% vs. 8% (NS))At 3 years:Asthma (mean: 23% vs. 1% ( P < 0.001)Recurrent wheezing (mean: 21% vs. 12% (NS))Karaman 2011 [44]TurkeyProspective study of 70 children, 40 with RSV and 30 with non-RSV bronchiolitis0–36 months oldWheezing not defined1–3Recurrent wheezing: 35% vs. 53.3% ( P = 0.064; NS)Escobar 2010 [39]USRetrospective cohort study of 71,102 children born ≥32 wGA1.7% with medically attended RSV <12 months oldRecurrent wheezing: combination of encounter events, patient diagnoses using ICD codes, and prescription patterns3Recurrent wheezing: 16.2% vs. 6.2% a Bont 2004 [35]NetherlandsProspective cohort study of 140 infants with RSV (29% born 25–36 wGA; 3% cardiac disease, 2% CLD)≤12 months oldRespiratory symptoms and wheezing episodes: parent-reported (daily log). Disease episode: presence of respiratory symptoms for ≥2 consecutive days3Wheezing: >50% decrease in first year of follow-up ( P < 0.001)Escobar 2013 [38]USRetrospective cohort study of 72,602 children born ≥32 wGA1.74% with medically attended RSV < 12 months old [0.69% hospitalized and 1.05% treated as outpatient)Recurrent wheezing: as in Escobar 2010 [39], using a combination of encounter events, patient diagnoses, and prescription patterns5Recurrent wheezing year 5: 12.5% vs. 4.6% a Recurrent wheezing year 3-5: 40.0% vs. 12.3% a Carbonell-Estrany 2015 [14]SpainMulticenter, observational, nested, case-control study of preterm (32-35 wGA) infants with RSV ( n  = 125) and controls ( n  = 362)<12 months oldRecurrent wheezing: ≥3 wheezing episodes within 12 months. Severe recurrent wheezing: recurrent wheezing associated with at least one episode of hospitalization, or ≥3 medical attendances or ≥1 courses of systemic steroids, or asthma medication for ≥3 consecutive months or 5 cumulative months in a year6At 6 years of age:Recurrent wheezing: 46.7% vs. 27.4% ( P = 0.001)Severe wheezing: 37.7% vs. 23.7% ( P = 0.010)Total wheezing: 71.4% vs. 54.4% ( P = 0.006)Zomer-Kooijer 2014...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent wheezing: ≥3 episodes of bronchial obstruction not verified by a physician1 and 3At 1 year:Asthma (mean: 11% vs. 0% ( P = 0.004)Recurrent wheezing (mean: 4% vs. 8% (NS))At 3 years:Asthma (mean: 23% vs. 1% ( P < 0.001)Recurrent wheezing (mean: 21% vs. 12% (NS))Karaman 2011 [44]TurkeyProspective study of 70 children, 40 with RSV and 30 with non-RSV bronchiolitis0–36 months oldWheezing not defined1–3Recurrent wheezing: 35% vs. 53.3% ( P = 0.064; NS)Escobar 2010 [39]USRetrospective cohort study of 71,102 children born ≥32 wGA1.7% with medically attended RSV <12 months oldRecurrent wheezing: combination of encounter events, patient diagnoses using ICD codes, and prescription patterns3Recurrent wheezing: 16.2% vs. 6.2% a Bont 2004 [35]NetherlandsProspective cohort study of 140 infants with RSV (29% born 25–36 wGA; 3% cardiac disease, 2% CLD)≤12 months oldRespiratory symptoms and wheezing episodes: parent-reported (daily log). Disease episode: presence of respiratory symptoms for ≥2 consecutive days3Wheezing: >50% decrease in first year of follow-up ( P < 0.001)Escobar 2013 [38]USRetrospective cohort study of 72,602 children born ≥32 wGA1.74% with medically attended RSV < 12 months old [0.69% hospitalized and 1.05% treated as outpatient)Recurrent wheezing: as in Escobar 2010 [39], using a combination of encounter events, patient diagnoses, and prescription patterns5Recurrent wheezing year 5: 12.5% vs. 4.6% a Recurrent wheezing year 3-5: 40.0% vs. 12.3% a Carbonell-Estrany 2015 [14]SpainMulticenter, observational, nested, case-control study of preterm (32-35 wGA) infants with RSV ( n  = 125) and controls ( n  = 362)<12 months oldRecurrent wheezing: ≥3 wheezing episodes within 12 months. Severe recurrent wheezing: recurrent wheezing associated with at least one episode of hospitalization, or ≥3 medical attendances or ≥1 courses of systemic steroids, or asthma medication for ≥3 consecutive months or 5 cumulative months in a year6At 6 years of age:Recurrent wheezing: 46.7% vs. 27.4% ( P = 0.001)Severe wheezing: 37.7% vs. 23.7% ( P = 0.010)Total wheezing: 71.4% vs. 54.4% ( P = 0.006)Zomer-Kooijer 2014...…”
Section: Resultsmentioning
confidence: 99%
“…Infants born prematurely are at risk of RSV-related sequelae, including recurrent wheezing [14, 39, 5457]. Data from a prospective study by Greenough et al [56] demonstrated that chronic respiratory morbidity occurs in preterm infants born between 32 and 35 weeks’ gestational age (wGA), regardless of whether their RSV infection required hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…Our research question was investigated among a group of patients experiencing the most severe disease since all required hospitalization, and these children experience the greatest morbidity in terms of subsequent wheezing and asthma 11, 12, 53 . High levels of medication adherence and retention of participants during follow-up further strengthen our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Most children infected with RSV experience mild disease that does not require hospitalization; nevertheless, RSV bronchiolitis is the leading cause of hospitalizations in infants younger than one year of age in the US 4, 5 . Early life RSV bronchiolitis is a major risk factor for subsequent recurrent wheezing and asthma 6–10 , and this risk is more profound among infants with severe bronchiolitis requiring hospitalization compared to infants with less severe bronchiolitis involving an outpatient encounter 11, 12 . Among a high risk group of infants hospitalized with RSV bronchiolitis, up to 90% of children experience 2 or more wheezing episodes and almost 50% will be diagnosed with asthma by the age of 6 years 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that children hospitalized for RSV bronchiolitis during infancy were more likely to have subsequent episodes of wheezing and asthma during the first decade of life compared with children without a history of a bronchiolitis hospitalization during infancy (Table 1) [911,3340]. In a 10-year follow-up study, Pullan and Hey reported that children with RSV bronchiolitis in infancy were more likely to have further episodes of wheezing compared with controls (42 vs 19%).…”
Section: Studies Of the Influence Of Rsv Infection On The Developmentmentioning
confidence: 99%